The Purpose of Sister City Collaboration between Malang and Fuqing, China - Utomo, Ario Bimo (Fakultas Ilmu Sosial and Ilmu Politik Universitas Jenderal Soedirman, 2024)
This study aims to explore the motifs behind the collaboration between Malang and Fuqing, China. Through the MRQ approach, this research analyzes how the motif of education emerges as a response to Fuqing's best practices in effective educational management. Furthermore, the study also identifies agricultural motifs driven by the significant potential of Fuqing as a soybean producer, aligning with Malang's characteristics as a tempeh producer. The results of the study indicate that the collaboration between Malang and Fuqing is driven by the real needs and potentials in both cities. This study successfully addresses research question (MRQ) number 3 regarding intercity cooperation through the lens of collaboration motifs. The implications of this research have a significant impact on strengthening the understanding of the dynamics of intercity cooperation, as well as providing a broader perspective on the importance of cross-regional collaboration in advancing local development.